The story of Apollonius, king of Tyre : a commentary - Panayotakis, Stelios, 1968- (Texte und Kommentare., 2012)
The anonymous Latin Story of Apollonius, King of Tyre (Historia Apollonii regis Tyri) is a romance of adventure, possibly of Greek origins, with Christian elements in its plot. Well known for its important afterlife, including Shakespeare's Pericles, the Story of Apollonius is commonly viewed as a Christianised folktale of a sub-literary character. This literary and philological commentary interprets the text within the framework of ancient prose fiction, Christian literary tradition, and pagan culture, and discusses in detail its language, style, and narrative technique.